Ethnopedagogical Learning Management Based on Banten Culture: An Innovation for Strengthening Early Childhood Character through the Integration of Digital Portfolios - Maya LaelaSari; Asep Muhyidin; Aan Asphianto; Ujang Jamaludin (Educia Journal, 2026)
The limited integration of local cultural values into early childhood education management has raised concerns regarding the effectiveness of character development programs in increasingly globalized societies. This study aimed to examine the effectiveness of an ethnopedagogical learning management model based on Banten local culture integrated with digital portfolios in strengthening early childhood character. A quantitative approach employing a quasi-experimental design with a non-equivalent control group was utilized. The study involved 130 children aged 4–6 years from several kindergartens in Banten Province, Indonesia, who were assigned to experimental and control groups. The intervention was implemented through a structured learning management model that incorporated local cultural values into planning, implementation, assessment, and stakeholder collaboration processes, while digital portfolios were used to document and monitor children's developmental progress. Data were collected using validated observation instruments measuring three dimensions of character development: discipline, empathy, and independence. The data were analyzed using descriptive statistics, normality and homogeneity tests, independent sample t-tests, and N-Gain analysis. The findings revealed a statistically significant difference between the experimental and control groups (p < 0.05). The experimental group achieved a high effectiveness category with an average N-Gain score of 0.75, compared to 0.32 in the control group. The results indicate that the integration of ethnopedagogical principles and digital portfolio systems contributes not only to improved character development but also to more culturally responsive and sustainable educational management practices. The study highlights the potential of culture-based learning management as a strategic approach for strengthening children's character while preserving local cultural identity in the digital era.